A walk down the red carpet: students as producers of digital video-based knowledge. (1st January 2013) - Ryan, Barry
Disengaged and apathetic students are common in many undergraduate classrooms. One approach to engage these students, and enhance the learning experience, is to integrate active learning into the curriculum. The purpose of this pedagogical evaluative study was to investigate if student researched, designed and created digital video could act as viable reusable peer learning resources. Although the use and integration of technology was central to the scope of this project, other ideas such as threshold concepts, the requirement for both active and authentic social constructivist learning, and student empowerment are pivotal to the rationalisation of this research. Overall, students appreciated an alternative method of learning; however, they were more reserved about their perceived learning and the usefulness of the peer-generated videos as learning resources. This pedagogical evaluative study suggests that practitioners can introduce student produced digital media as an alternative student centred learning approach whilst simultaneously developing student soft skills.